2020
DOI: 10.1016/j.trf.2020.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural differences in driver aggression, aberrant, and positive driver behaviors

Abstract: The present study investigated differences in driver aggression for self and others within countries and cultural differences between driver aggression, aberrant, and positive driver behaviors across five countries (Estonia, Greece, Kosovo, Russia, and Turkey). It was pre-dicted that drivers from these five countries differ significantly in terms of driver aggres-sion for self and others, aberrant, and positive driver behaviors. In the study, 743 participants completed the questionnaire package, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…For instance, Turkish pedestrians showed more transgression, lapses and aggressive behaviours compared to Estonian and Russian pedestrians. Moreover, Turkish pedestrians showed more positive behaviours than Kosovar pedestrians (Solmazer et al, 2020). Moreover, Deb et al (2017) confirmed that the PBS is a reliable measure of pedestrian accident involvement and found that violations were related to higher involvement in accidents with injuries.…”
Section: Pedestrian Behaviours and Road Safetymentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, Turkish pedestrians showed more transgression, lapses and aggressive behaviours compared to Estonian and Russian pedestrians. Moreover, Turkish pedestrians showed more positive behaviours than Kosovar pedestrians (Solmazer et al, 2020). Moreover, Deb et al (2017) confirmed that the PBS is a reliable measure of pedestrian accident involvement and found that violations were related to higher involvement in accidents with injuries.…”
Section: Pedestrian Behaviours and Road Safetymentioning
confidence: 96%
“…The scale was based on the framework that has been used to measure aberrant driver behaviours (Lawton, Parker, Manstead, & Stradling, 1997;Reason, Manstead, Stradling, Baxter, & Campbell, 1990), and positive driver behaviours (Özkan & Lajunen, 2005). The PBS was used as a reliable and valid instrument for the investigation of pedestrian behavi-ours in different countries such as France (Granié et al, 2013), China (Qu, Zhang, Zhao, Zhang, & Ge, 2016;Xu, Ge, Qu, Sun, & Zhang, 2018), and Turkey (Demir, 2017;Solmazer et al, 2020).…”
Section: Pedestrian Behaviours and Road Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes researchers analyze only the effect of culture on attitudes and behavior, controlling for the effect of gender (44,52,53). Only one study to date analyzes gender differences in several countries, but only on young driver behaviors and attitudes (22).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies sometimes include an analysis of gender differences, but only on a country-by-country basis, or on the overall sample ( 4851 ). Sometimes researchers analyze only the effect of culture on attitudes and behavior, controlling for the effect of gender ( 44 , 52 , 53 ). Only one study to date analyzes gender differences in several countries, but only on young driver behaviors and attitudes ( 22 ).…”
Section: Literature Reviewmentioning
confidence: 99%